Meningkatkan Kreativitas Anak melalui Penggunaan Media Plastisin pada Peserta Didik Kelompok B2 TK Negeri Pembina Mataram - Ternihi, Sang Ayu Kadek (ARZUSIN, 2022)
The research objective to be achieved in this study is to determine the use of plasticine media to increase children's learning creativity in group B2 students of Mataram State Kindergarten in Odd Semester for the 2021/2022 Academic Year. The subjects of this study were 14 students of the B2 TK Negeri Pembina Mataram group, consisting of 8 female students and 6 male students. This research uses action research in two cycles consisting of four stages, namely: design, activity and observation, reflection. From all the activities of implementing the action research of students in the B2 TK Negeri Pembina Mataram group, namely observing teacher activities and observing student activities in cycle I and cycle II. Thus the increase in teacher activity in learning has increased from 71.88% from the first cycle to 90.63% in the second cycle. Student activity also increased by 72.50% in the first cycle to 87.50% in the second cycle. Student mastery of learning materials showed an increase. This is evidenced by the average value of the daily test results (the average daily test without the use of plasticine media is 77.07 to 81.24 and to 88.36 after the use of plasticine media. And the completeness value of learning the use of plasticine media is 64.29% to 78.57% and to 100% after the use of plasticine media.